WAQE: a Web Application Quality Evaluation model. (4th December 2006) - Mavromoustakos, S.; Andreou, A.S.
Developing and maintaining web applications that have high quality demands the provision of certain assessment and monitoring mechanisms to afford such a success. Continuous evaluation of the web applications to check if they meet functional and non-functional requirements, as well as the organisational goals, necessitates the use of quality evaluation models in a fast-changing environment. This paper proposes an efficient web application quality evaluation model that is based on two axons: internal (within the organisation) and external (the users). The model places emphasis on quality issues as defined by ISO 9126 and other web quality factors and utilises importance-based criteria for evaluating requirements. Finally, the applicability and efficiency of the model are demonstrated through the evaluation of two different types of web applications.